Child Health and Surgery: A Challenge for Future Clinical Research - Gloria Pelizzo; Valeria Calcaterra (Children, 2022)
Pediatric surgical conditions cross a broad range of disease categories and includes injuries, infections, tumors, rare disease and congenital anomalies [...]